'Whoever Has the Stick Guides the Buffalo': Neutrality, Party Politics and Authority Formation in Community Mediation in the Central and West Terai, Nepal. (April 2016) - Suykens, Bert; Stein, Danielle
This article examines the relationship between the concept of neutrality in community mediation and partisan party politics in Nepal. Focusing on one donor-sponsored, US model-based community mediation programme in the Terai, this article contributes to a growing literature on authority formation and the role of party politicians in post-conflict Nepal. It argues that both neutrality and bias in dispute settlement are constitutive of building (Weberian) authority, allowing for the legitimate exercise of power by politicians. Neutrality is not only highly valued in mediation ideology, but is also a crucial legitimizing register in dispute settlement in Nepal. Although resolving disputes neutrally enhances the local legitimacy of (political) mediators, our research finds that there are cases when showing political favouritism also helps maintain power. We find that these contradictory incentives and the need to balance them guide the arena in which politicians choose to resolve disputes and how they choose to resolve them. These strategic decisions made by politicians in order to balance neutrality and bias thus guide outcomes of dispute settlement, and mediation in particular. This raises questions about the proclaimed ability of community mediation to overcome power imbalances and provide justice to disadvantaged communities.